A Rare Case of Intramuscular Schwannoma of Dorsal Ramus Nerve: A Case Report (Indian Journal of Case Reports, 2021)
Schwannoma is a benign, expansile neoplasm that originates from nerve sheaths. Intramuscular schwannoma is a rare tumor presenting as a slow-growing soft-tissue mass that may or may not has associated neurological symptoms. We present a rare case of intramuscular schwannoma of the dorsal ramus nerve in a 50-year-old female patient who presented with a single, firm, and well-defined swelling over the back region. On magnetic resonance imaging, a 54 mm × 23 mm × 20 mm, well-defined altered signal intensity lesion at the left posterior paraspinal region extending from the superior endplate of D12 to the inferior endplate of L1 vertebral bodies was noted which was suggestive of neurogenic tumor/ hemangioma. The swelling was excised and sent for histopathological examination (HPE). A diagnosis of intramuscular schwannoma was confirmed on HPE. Hence, all soft-tissue tumors should be sent for HPE for confirmation of the diagnosis and its further management.